2019
DOI: 10.1111/aor.13422
|View full text |Cite
|
Sign up to set email alerts
|

Bionic hand as artificial organ: Current status and future perspectives

Abstract: Even though the hand comprises only 1% of our body weight, about 30% of our central nervous systems (CNS) capacity is related to its control. The loss of a hand thus presents not only the loss of the most important tool allowing us to interact with our environment, but also leaves a dramatic sensory-motor deficit that challenges our CNS. Reconstruction of hand function is therefore not only an essential part of restoring body integrity and functional wholeness but also closes the loop of our neural circuits di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 81 publications
0
16
0
1
Order By: Relevance
“…Quality of life and hand function showed poor to very poor results. Hand Bionic Score was 19, recommending a bionic prosthesis fitting with amputation of the nonfunctioning hand radically [63]. For instance, a special topic is sensation of the prosthesis-while currently available prostheses need visual feedback to control movements, further development of prosthesis sensation could improve dexterity of prosthetic hands [64].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life and hand function showed poor to very poor results. Hand Bionic Score was 19, recommending a bionic prosthesis fitting with amputation of the nonfunctioning hand radically [63]. For instance, a special topic is sensation of the prosthesis-while currently available prostheses need visual feedback to control movements, further development of prosthesis sensation could improve dexterity of prosthetic hands [64].…”
Section: Discussionmentioning
confidence: 99%
“…Opposition movement of the thumb is the crucial function which makes the human hand unique. Accordingly, impairment is not only disastrous for accomplishing daily life activities and occupational tasks, sometimes leading to psychological burden, but also has socioeconomic consequences (15).…”
Section: Discussionmentioning
confidence: 99%
“…Martin Aman et al of the Medical University of Vienna, Vienna, Austria reported on their efforts to restore meaningful function to the hand by complex mechatronic replacement that have functional capabilities that in some respects even outperform biological alternatives. As with replantation and transplantations, the challenge of bionic replacement is connecting the target with the central nervous system to achieve natural and intuitive control.…”
Section: Orthopedic Supportmentioning
confidence: 99%